Transcriptional analysis of the human PAX9 promoter - Carolina Vieira de Almeida; Simone Caixeta de Andrade; Cristiane Pereira Borges Saito; Liza Lima Ramenzoni; Sergio Roberto Peres Line (University of São Paulo, 2010)
OBJECTIVES: PAX9 belongs to the Pax family of transcriptional factor genes. This gene is expressed in embryonic tissues such as somites, pharyngeal pouch endoderm, distal limb buds and neural crest-derived mesenchyme. Polymorphisms in the upstream promoter region of the human PAX9 have been associated with human non-syndromic tooth agenesis. In the present study, we verified the in vitro mRNA expression of this gene and the luciferase activity of two constructs containing promoter sequences of the PAX9 gene. MATERIAL AND METHODS: Embryonic tissues were obtained from digits, face, and midbrain/hindbrain regions. Fragments containing PAX9 promoter sequences were cloned into reporter plasmids and were transfected into the different cell cultures. mRNA were extracted from primary cell cultures. RESULTS: The semi-quantitative RT-PCR results showed that in vitro E13.5 limb bud and CNS cells express PAX9, but cells derived from the facial region do not. Moreover, the luciferase assay showed that protein activity of the constructed vector was weaker than pgl3 -basic alone. CONCLUSIONS: The present results suggest that the promoter sequences analyzed are not sufficient to drive PAX9 gene transcription.